Polymeric Vehicles for Controlled Delivery of Ayurvedic Drugs for Wound Management - Biswas A.; Maiti P.; Sahu M. (My University, 2025)
The wound healing is a composite phenomenon as it passes through many intricate phases, where cell-to-cell and cell-to-matrix interactions are very crucial. Due to the complexity of wounds, different types of dressing materials are needed for faster healing. The traditional herbal medicines have a long history for wound management but often suffer from their low bioavailability and proper matrix materials to hold the drug. There are various dressing materials available in the market, but the efficient dressing materials using Ayurvedic drugs are one of the important aspects in the present-day scenario. The wound management using different herbal drugs loaded dressing materials will be emphasized in this chapter. The encapsulation of herbal drug in polymer matrix increases their efficiency toward wound healing. Polymeric dressing materials have been discussed in details with their efficacy in terms of ex vivo, in vivo and clinical studies. Different forms of modern dressing materials include hydrogels, patch and scaffolds which will shed light in terms of their relative efficacy. Finally, in vivo and clinical studies have been presented showing better wound management using traditional herbal drugs. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.